Product Development of Bir Pletok (Betawinese Traditional Drink) with Coffee and Vanilla Flavor for Dip Bag Application - pricilia, glorya; noer fadhillah, hendry; nurkhoeriyati, tina (Liaison Journal of Engineering, 2023)
Bir Pletok is a Betawinese traditional drink made of spices such as ginger, secang wood, cinnamon, pandan leaves, lime leaves, cloves, lemongrass, star anise, nutmeg, cardamom, and mesoyi wood. Due to its spice and herbs ingredients, this Betawinese traditional drink potentially has health benefits. However, as one of the non-objects of Indonesian cultural heritage, this beverage needs to be preserved its existence. Thus, this research aims to determine the optimal formulation of Bir Pletok based on consumer behavior and preference market assessment following consumer acceptance and quality (sensory, microbiology, and antioxidant activity). The market assessment, done through online questionnaires among DKI Jakarta residents, revealed that respondents who prefer Bir Pletok with coffee and prefer to drink traditional drinks that are easy to consume comprised the highest percentage. The percentage of DPPH inhibition of selected treatment 3 (T3) (8.1% ginger, 0.2% vanilla, and 6.2% coffee) was significantly higher, and the IC50 was significantly lower than the control. These results imply that T3 had a higher antioxidant activity than the control. Both control and T3 met the requirements of the total number of microbes and yeast molds referring to SNI regarding herbs and spices. In addition, the pH value results show that Bir Pletok averaged below the value of around 5.0. Keywords: Antioxidant activity, Bir Pletok, Consumer Behavior and Perceptions, DPPH, Sensory Analysis, Total Plate Count.